Authentic Interpretation of The Hadith 'You Know Better About Your Worldly Affairs' - Arfan, Arfan; Muhammadiyah Amin; La Ode Ismail Ahmad; A., Nur Afni (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2024)
This study aims to generate an authentic interpretation of the hadith "You know better about your worldly affairs," analyzed from the aspects of sanad (chain of narration), matan (text), cause of revelation, and intertextuality with Quranic verses and other hadiths. The research method employs a qualitative approach with library research. Data is collected through in-depth study of authentic hadith and tafseer literature. Data analysis techniques apply an interactive content analysis model covering data reduction, data display, drawing and verifying conclusions. The findings reveal that human life is divided into two domains: the hereafter (faith and worship) which must be guided by Islamic texts, and the worldly domain (etiquette and transactions) which is further divided into matters that have been regulated in detail in the texts and matters that have not. The hadith about "you know better about your worldly affairs" belongs to the latter category which has no detailed regulations from the syariah. Although general ('aam) in meaning, this hadith only applies to areas without detailed rules from the syariah. Thus, the Prophet's ijtihad could be right or wrong in this domain. This does not contradict Surah al-Najm:3-4 since it pertains specifically to the Quran's truth, not all sayings of the Prophet. Therefore, an authentic interpretation is obtained in line with the research objectives. Penelitian ini bertujuan menghasilkan interpretasi autentik atas hadis “Kalian lebih paham tentang urusan dunia kalian”, dikaji dari aspek sanad, matan, sebab wurud, dan intertekstualitas dengan ayat al-Quran dan hadis lain. Metode penelitian menggunakan kualitatif dengan pendekatan kepustakaan. Data dikumpulkan melalui telaah mendalam pada literatur hadis dan tafsir otentik. Teknik analisis data menerapkan content analysis model interaktif meliputi reduksi data, penyajian data, serta penarikan dan verifikasi simpulan. Hasil penelitian menemukan bahwa kehidupan manusia terbagi dua wilayah: ukhrawi (akidah dan ibadah) yang harus berpedoman pada nas, dan duniawi (adab dan muamalah) yang terbagi lagi menjadi yang telah diatur secara rinci dalam nas dan yang belum. Hadis tentang “kalian lebih paham urusan dunia” termasuk kategori kedua yang belum diatur rinci. Meskipun bersifat ‘ām, hadis ini hanya berlaku pada bidang tanpa aturan rinci dari syariat. Maka ijtihad Nabi bisa benar dan bisa salah. Hal ini tidak bertentangan dengan QS al-Najm:3-4 karena berkaitan dengan kebenaran al-Qur’an, bukan semua ucapan Nabi. Dengan demikian, diperoleh interpretasi autentik sesuai tujuan.